Padronização e reprodutibilidade de um protocolo de avaliação da capacidade coordenativa: tempo de reação - Marotto, Luciano Pereira [UNIFESP] (2016)
Introduction: The purpose of the athletes is to achieve the perfect biomechanical motion with the lowest caloric expenditure. Assessments of physical and physiological capabilities are used for a long time and is intended to provide the necessary treinadoresinformações in the development of increasingly specific training. The reaction time (RT) is part of all the coordinative abilities that characterize the process of sensorimotor learning and control of movements and is the performance measure most commonly used to measure, evaluate and compare the performance of human movement (Weineck 1999 ). However, the methodological models used bump, for the most part, the lack of standardization. The tests that purport to measure the TR should disregard or minimize the participation of the movement performed by the member that will provide the reading of the reaction time, and ensure that the processing time of the equipment used is not built in time is the variable. Objective: This study aims to propose a protocol to test the variable reaction time grounded in objectivity criteria, reprodutibilidadee validity. Methods: The study included 733 healthy individuals between the ages of 6 and 83 years, with 278 females and 455 males, representing 38% and 62% of the sample, respectively, and divided into five groups based on the classification chronological proposed by Gallahue (1999). evaluation was carried out anthropometric (weight, height and body fat percentage) in all participants to characterize the sample and then all underwent assessment protocol reaction time at two different times with one week interval.The method consisted of a standard heating five movements coordinative and oriented in a space of 10 meters; later the subjects were positioned at a distance of three meters from the equipment, in a standing position, and after the stimulus reaction time was measured from the heel movement. The equipment used was exclusively dedicated to the routine measurement of TR, ensuring that the reaction time did not suffer interference from the equipment of processing time. Results: The protocol showed good reproducibility has been strong correlation with ICC> 0.8 in groups , with the exception of G3 (aged 20 to 40 years) who presented moderate correlation with CCI 0.6-0.8. The APPRAISAL method TR presented validity, as demonstrated by the criteria of face validity, based on the theoretical concepts of TR and construct validity, shown in statistically significant difference shown between G3 (aged 20 to 40 years) and G5 (the age of 60 years). Conclusion: We conclude that the proposed method exclusively dedicated to measuring more accurately reaction time protocol achieved its purpose, with reproducibility and validity. However, more studies are needed so that we can better understand the variable behavior during the different stages of life.